Oxygen Ions O+ Energized by Kinetic Alfvén Eigenmode During Dipolarizations of Intense Substorms. Issue 11 (14th November 2017) - Duan, Suping; Dai, Lei; Wang, Chi; He, Zhaohai; Cai, Chunlin; Zhang, Y. C.; Dandouras, I.; Reme, H.; André, M.; Khotyaintsev, Y. V.
Abstract: Singly charged oxygen ions, O +, energized by kinetic Alfvén wave eigenmode (KAWE) in the plasma sheet boundary layer during dipolarizations of two intense substorms, 10:07 UT on 31 August 2004 and 18:24 UT on 14 September 2004, are investigated by Cluster spacecraft in the magnetotail. It is found that after the beginning of the expansion phase of substorms, O + ions are clearly energized in the direction perpendicular to the magnetic field with energy larger than 1 keV in the near‐Earth plasma sheet during magnetic dipolarizations. The pitch angle distribution of these energetic O + ions is significantly different from that of O + ions with energy less than 1 keV before substorm onset that is in the quasi‐parallel direction along the magnetic field. The KAWE with the large perpendicular unipolar electric field, Ez ~ −20 mV/m, significantly accelerates O + ions in the direction perpendicular to the background magnetic field. We present good evidences that O + ion origin from the ionosphere along the magnetic field line in the northward lobe can be accelerated in the perpendicular direction during substorm dipolarizations. The change of the move direction of O + ions is useful for O + transferring from the lobe into the central plasma sheet in the magnetotail. Thus, KAWE can play an important role in O + ion transfer process from the lobe into the plasma sheet during intense substorms. Key Points: Energetic O + ion (>1 keV) flux increases significantly during intense substorm ( AE  > 500 nT) dipolarizations O + ions are energized by KAWE mostly in the direction perpendicular to the magnetic field in the PSBL KAWE can play an important role in the process of O + ions transferred from the lobe/PSBL into the plasma sheet during intense substorms